1985
DOI: 10.1002/jmv.1890150105
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus markers in children with acute leukemia: The effect of chemotherapy

Abstract: Hepatitis B virus markers were tested in the serum of 49 children with acute leukemia on clinical presentation and during subsequent chemotherapy. Hepatitis B surface antigenemia was observed in only six patients (12%), none of whom progressed to chronic infection. Chemotherapy had a marked suppressive effect on the production of antibodies to hepatitis B virus antigens and overt infection occurred in two children after suppression of protective immunity. Evidence of liver damage was frequently observed and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

1985
1985
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 8 publications
1
13
1
Order By: Relevance
“…The incidence of chronic HBV infection in children with leukemia was higher in this multicentric study compared to that found in similar patients collected in one unit only [13]. This could be due to epidemiological differences, since patients from different regions of Italy were included in this study.…”
Section: Discussioncontrasting
confidence: 75%
“…The incidence of chronic HBV infection in children with leukemia was higher in this multicentric study compared to that found in similar patients collected in one unit only [13]. This could be due to epidemiological differences, since patients from different regions of Italy were included in this study.…”
Section: Discussioncontrasting
confidence: 75%
“…There are only few reports of hepatic damage attributed to cyclophospamide [20,21] or doxorubicin [22]. In many of the previous studies viral hepatitis has obscured the hepatotoxic effects of the chemotherapeutic agents by inducing chronic liver disease in patients treated for leukemia [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…6 Moreover, immunosuppressive therapy, to which these patients are submitted, can play an important role, since it predisposes to higher levels of viral replication in organs where the virus can persist only in normal circumstances. 7 The increase in hepatitis B viral replication also has been shown to occur in patients taking chemotherapy 9,10 and corticosteroids. 11,12 However, acute pancreatitis that was developed in healthy HBV carriers with spontaneous acute exacerbation of chronic HBV infection is rare.…”
Section: Discussionmentioning
confidence: 99%